A new E. coli O group O158 associated with an outbreak of infantile enteritis. Issue 10 (October 1974) - Rowe, B.; Gross, R. J.; Lindop, R.; Baird, R. B.
Abstract : An outbreak of acute diarrhoea occurred amongst babies in a special care baby unit. Thirteen babies were at risk; six suffered diarrhoea and three of these died. An Escherichia coli with an unidentifiable O antigen and flagellar antigen H23 was isolated from all six cases. This O antigen has been accepted into the international scheme as O158.